Pengaruh Personal Selling dan Brand Image Terhadap Keputusan Konsumen dalam Memilih Asuransi Kendaraan - Darda, Ahmad; Rojikun, Ahmad (CV. ULIL ALBAB CORP, 2024)
This study aims to analyze the influence of personal selling and brand image on consumer decisions in choosing vehicle insurance products. Using a quantitative approach, data were obtained from 100 respondents through a questionnaire designed to measure their perceptions related to these two independent variables. The regression analysis results show that both personal selling and brand image significantly influence consumer decisions. Personal selling plays a major role in building trust through direct interaction, while brand image has an important impact on consumer perceptions of the quality and reputation of the insurance products. A coefficient of determination of 66% indicates that the combination of these two variables explains the majority of consumer decisions, while the remainder is influenced by other factors. These findings emphasize the importance of managing effective marketing strategies to enhance vehicle insurance penetration in Indonesia.